2008
DOI: 10.1152/ajplung.90210.2008
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMPK attenuates neutrophil proinflammatory activity and decreases the severity of acute lung injury

Abstract: AMP-activated protein kinase (AMPK) is activated by increases in the intracellular AMP-to-ATP ratio and plays a central role in cellular responses to metabolic stress. Although activation of AMPK has been shown to have anti-inflammatory effects, there is little information concerning the role that AMPK may play in modulating neutrophil function and neutrophil-dependent inflammatory events, such as acute lung injury. To examine these issues, we determined the effects of pharmacological activators of AMPK, 5-ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
257
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 271 publications
(279 citation statements)
references
References 65 publications
13
257
1
8
Order By: Relevance
“…AICAR is metabolized to 5-aminoimidazole-4-carboxamide ribonucleoside, which mimics all effects of AMP on AMPK systems (23,34). Zhao et al, (35) have shown that AICAR-mediated AMPK activation reduced endotoxininduced acute lung injury in mice. Another study showed that administration of AMPK activator metformin (anti-diabetic drug) increased the survival rate of endotoxemic mice (36).…”
Section: Discussionmentioning
confidence: 99%
“…AICAR is metabolized to 5-aminoimidazole-4-carboxamide ribonucleoside, which mimics all effects of AMP on AMPK systems (23,34). Zhao et al, (35) have shown that AICAR-mediated AMPK activation reduced endotoxininduced acute lung injury in mice. Another study showed that administration of AMPK activator metformin (anti-diabetic drug) increased the survival rate of endotoxemic mice (36).…”
Section: Discussionmentioning
confidence: 99%
“…Although metformin has a broad spectrum of effects, inhibition of mitochondrial complex I and activation of 5' adenosine monophosphate-activated protein kinase (AMPK) appear to be major mechanisms of its action (25,26). Recent studies have shown that besides their ability to regulate cellular metabolism (27), metformin and other AMPK activators can decrease the severity of organ injury in acute inflammatory states (28), including LPS-induced liver injury or acute lung injury (29,30). Metformin, berberine or aminoimidazole carboxamide ribonucleotide (AICAR) were all shown to diminish activation of the tolllike receptor 4 (TLR4)/NF-κB signaling cascade, as well as to release of proinflammatory mediators of neutrophils and macrophages, and also to enhance endothelial integrity in vitro and in models for sepsis (31)(32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…The AMPK activator, 5-amino-4-imidazole-carboxamideriboside (AICAR), has been demonstrated to reduce the severity of airway inflammation in murine experimental models of asthma and lipopolysaccharide (LPS)-induced acute lung injury [8,9]. Moreover, the AMPK agonist metformin, currently the most widely prescribed oral blood glucoselowering agent, has been reported to decrease the levels of plasma inflammatory indices, such as C-reactive protein (CRP) [10].…”
Section: Introductionmentioning
confidence: 99%